In the Conditions of Uzbekistan Principal Principles of Organization of Culture and Recreation Parks - Karimov Ulugbek Nurmamatovich; Musurmonova Munira Musurmonqizi (International Journal on Integrated Education, 2022)
The article scientifically and theoretically examines the basic principles of the design of "Parks of Culture and Recreation", in particular, the criteria for the formation of parks in the conditions of Uzbekistan. Summary and sketch drawing are attached